Antimicrobial resistance of clinical bacterial isolates according to the WHO’s AWaRe and the ECDC-MDR classifications: the pattern in Ghana’s Bono East Region - Walana, Williams; Vicar, Ezekiel Kofi; Kuugbee, Eugene Dogkotenge; Sakida, Francis; Yabasin, Iddrisu Baba; Faakuu, Eric; Amfoabegyi, Solomon; Ziem, Juventus Benogle (Frontiers in Antibiotics, 2023)
Antimicrobial resistance (AMR) stays a significant health challenge globally and nations have the responsibility to maintain constant surveillance of AMR, particularly the emergence of multidrug resistance (MDR) strains to existing antibiotics. Against this backdrop, we applied the WHO AWaRe (ACCESS, WATCH, RESERVE) antibiotics classification and the European Centre for Disease Prevention and Control (ECDC) MDR definition to AMR isolates from clinical specimens. This study retrieved bacterial culture and antibiotic sensitivity tests outcomes. These results were grouped according to the AWaRe and ECDC-MDR classifications. In all, the culture and sensitivity results of 3178 clinical specimens were investigated, of which 59.5% were from female patients. Pathogens were isolated from 1187 specimens (37.4%). Among the WHO's ACCESS antibiotics, tetracycline showed a relatively high insusceptibility, particularly observed in Gram positive (GP) isolates (66.7% to 76.7%), augmentin (44.7% to 81.3%), and cloxacillin (50.0% to 78.1%). However, the Gram negative (GN) isolates showed relatively high level of susceptibility to amikacin, augmentin, and nitrofurantoin. For the WHO WATCH antibiotics, cefuroxime, ceftriaxone, cefotaxime, and ciprofloxacin showed relatively high level of nonresponsiveness to the GN isolates, particularly Proteus (31.4% to 78.4%), Pseudomonas (21.4% to 96.4%), and Enterobacter (62.5% to 100%) spp. Among the WHO's RESERVE antibiotics, resistance to ceftazidime was commonly associated with the GN isolates coliforms, Eschericha coli, Klebsiella and Citrobacter spp. Insusceptibility to meropenem was frequent in Staphylococcus spp., E. coli, coliforms, and Proteus spp. Out of the 1187 isolates, 15.5% (184) were GAT (gentamycin, ampicillin, tetracycline) MDR, of which 61% (112/184) were from females. The most predominant GAT-MDR isolates were Staphylococcus spp., E. coli, coliforms, and Klebsiella spp. In conclusion, the study revealed a relatively high and diverse AMR. However, MDR per the ECDC definition was relatively low. There is therefore the need to have expanded research on AMR to inform national criteria for MDR in Ghana.